2014
DOI: 10.1016/j.paid.2014.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural perception of trustworthiness: The effect of ethnicity features on evaluation of faces’ observed trustworthiness across four samples

Abstract: This is the accepted manuscript of an article published as: Cross-cultural perception of trustworthiness: the effect of ethnicity features on evaluation of faces' observed trustworthiness across four samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 27 publications
6
47
0
Order By: Relevance
“…The present results expand on this finding by showing the effect of facial trustworthiness on people’s trust behavior for both same- and other-race faces. Though some previous studies found other-race partners were perceived as more risky than were same-race partners ( Blair et al, 2004 ; Eberhardt et al, 2006 ), our results are consistent with previous findings of cross-cultural homogeneity regarding facial judgments ( Mcarthur and Berry, 1987 ; Zebrowitz et al, 1993 ; Birkás et al, 2014 ). For instance, an online trust game among Arab and German participants relied on similar facial features to judge trustworthiness cross culture ( Bente et al, 2014 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present results expand on this finding by showing the effect of facial trustworthiness on people’s trust behavior for both same- and other-race faces. Though some previous studies found other-race partners were perceived as more risky than were same-race partners ( Blair et al, 2004 ; Eberhardt et al, 2006 ), our results are consistent with previous findings of cross-cultural homogeneity regarding facial judgments ( Mcarthur and Berry, 1987 ; Zebrowitz et al, 1993 ; Birkás et al, 2014 ). For instance, an online trust game among Arab and German participants relied on similar facial features to judge trustworthiness cross culture ( Bente et al, 2014 ).…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies showed that the trustworthiness evaluations rely on the face shape, not ethnicity. Actually, own-race faces were rated as trustworthy as other-race faces ( Xu et al, 2012 ; Birkás et al, 2014 ; Sofer et al, 2017 ; Strachan et al, 2017 ). Therefore, we expected that the two types of SES information would modulate facial judgment and trust behavior, but race would not.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, face-based trustworthiness judgments are high in agreement among adults (Oosterhof and Todorov, 2008 ; Todorov et al, 2008 ). This agreement occurs even when the faces in question belong to a race with which adults are entirely unfamiliar (Xu et al, 2012 ; Birkás et al, 2014 ). A recent study reports that older and younger adults displayed similar levels of within-age agreement in their impressions of trustworthiness (Zebrowitz et al, 2013 ).…”
Section: Introductionmentioning
confidence: 98%
“…Specifically, babyface (young age) and old face (old age) enjoyed the higher level of trustworthiness when compared with an adult face (middle age) due to the baby-face overgeneralization effect, a stereotype that children are unreliable witnesses [ 38 , 59 ]. Furthermore, although the evolution of signaling has shown human might consciously adapt visual cues or characteristics to emphasize or conceal heritable facial traits, influencing social perception and recognition, different ethical or cultural groups (e.g., Chinese vs. Canadian [ 42 ] or Caucasian vs. African vs. East Asian vs. South Asian [ 35 ]) tended to share and adopt similar facial cues to judge trustworthiness and attractiveness. However, some ethnic groups (e.g., Hungarians) [ 35 , 38 ] or their implicit ethical attitude [ 63 ] might be biased toward their own facial ethnicity.…”
Section: Discussionmentioning
confidence: 99%